An analytical study of servant leadership and its effectiveness for employees at the College of Physical Education and Sports Sciences - Sumer University - Ali Fadel Salem (Global Scientific Publishing, 2023)
Institutions, particularly educational ones, are grappling with challenges arising from the rapid advancements in science and technology in our era. This has prompted leaders to seek modern management methods, including servant leadership. Unlike traditional top-down leadership, servant leadership is built on the philosophy of leaders serving their followers and prioritizing organizational goals. It stands out as an ethical leadership model rooted in spiritual values, focusing on meeting subordinates' needs and adapting to changing times, thereby supporting and motivating educational institution development. Servant leadership, a modern management model, emphasizes achieving goals through cooperation, coordination, and equitable work distribution among all institution members. It aligns with the concept of administrative intelligence, encompassing the mental and emotional capabilities of leaders to execute administrative tasks and handle subordinates effectively.
Keywords: Servant Leadership; Educational Institutions Administrative